Efeitos do rompimento da barragem de Fundão em Mariana no resultado das eleições de 2016 - Fontela, Bruna de Souza (Universidade do Vale do Rio dos Sinos, 2020)
Brazil is a country of continental proportions. Due to its situation, it can be widely affected by disasters, either natural or technological ones. Amongst the biggest disasters in Brazil’s history, we have the rupture of Fundão’s Dam in the city of Marina, Minas Gerais, in 2015. Causing deep economic and environmental impacts, this catastrophe impacted the Rio Doce’s Bay in an irreversible manner. As widely shown in the literature, these disasters can impact a place in various ways, it can severely reduce the production factors, cause deep environmental impacts and it can even change the election outcomes. With that in mind, this dissertation seeks to evaluate, through the Difference in Differences method, if what happened in Mariana had any effects on incumbent’s performances in the 2016’s municipal elections. The results have shown a negative and significantly impact on incumbent’s performance in municipalities that have local radio stations. It has also shown that candidates were rewarded by the population with a higher number of votes when they ran for reelection in municipalities that had a contingency plan for emergencies. These evidences promote a discussion on how technological disasters affect the electoral performance.
Keywords: Desastre tecnológico; Mariana; Desempenho eleitoral; Technological disaster; Electoral performance; ACCNPQ::Ciências Sociais Aplicadas::Economia